Coupling photo and sono technologies with BDD anodic oxidation for treating soil-washing effluent polluted with atrazine - Vieira dos Santos, E.; Sáez, C.; Cañizares, P.; Rodrigo, M. A.; Martínez-Huitle, C. A. [UNESP] (The Electrochemical Society, 2018)
In this work, it was studied the treatment of soil washing effluents coming from the remediation of a soil spiked with atrazine by using photolysis, sonolysis, electrolysis as well as photo- and sono- electrochemical technologies using diamond anodes. Results clearly showed that both irradiated technologies were more efficient than the single electrolytic technology and these can become a good alternative for the treatment of these effluents. Main characteristic of the effluents produced in the soil washing depended strongly on the ratio surfactant/soil. And, as a novel catalytic effect, the production of persulfate from the sulfate released during the oxidation of SDS played an important role in the oxidation mechanisms of this type of pollutants. Then, SDS can be proposed as an auxiliary reagent to be introduced in the effluent when emulsion is present to increase the efficiency of the electrochemical approach used.